LEGAL PROTECTION FOR DEBTORS OF ONLINE LOANS - Dwipayana, Dimas Pramodya (Legal Standing : Jurnal Ilmu Hukum, 2020)
Business concepts has experienced change from conventional (offline) to that which is digital (online) to win the market. This includes businesses in the financial technology (FinTech). This research aims to analyze the quality of loans in Indonesia FinTech-Peer to Peer (P2P) Lending. The objects of this research are seventy-two companies which establish FinTech-P2P lending. The tool used in this research is the analysis of the loan quality and the data trend from January until October 2018. Results of this research show that borrower and lender accounts have increased by 10,8 times, and it has increased by 1,8 times compared to the previous year. P2P lending has distributed loans as much as Rp.15.990.143.141.355 until October 2018. This number has grown 5,3 times since January of that year. Most of the loans in the P2P lending are current loans, in which its monthly payment is less than 30 days past due as of any date of determination. On average, the loan quality in the P2P lending is dominated by current loans, which reach 97,09%. The rest are non-current loans (1,90%) and bad loans (1,03%) every month. The low rate of non-performing loans shows a good quality of financial transaction. The information from this research may be used as a consideration for the society in using FinTech-P2P Lending for lending funds and investment.